Land of the lotus eaters - Johnstone, Harry (Financial Times, 2018)
I n the cool interior of his troglodyte cave, Ali Diglish is speaking at full tilt. The 26-year-old guide from Chenini barely draws breath. Like much of the country ...
Keywords: Récits de voyage -- Djerba

2500 km à vélo jusqu'à Djerba (Ouest-France, 2018)
Entretien Chantal, 63 ans, et Jean-Paul Allard, 71 ans, sont partis d'Aizenay, dimanche 2 septembre, direction Djerba. Quelle est l'origine de votre défi ? Chantal Allard : D'une part ...
Keywords: Récits de voyage -- Djerba